Development of full carbon wheels for sport cars with high-volume technology. (15th May 2018) - Rondina, Francesco; Taddia, Sara; Mazzocchetti, Laura; Donati, Lorenzo; Minak, Giangiacomo; Rosenberg, Philipp; Bedeschi, Andrea; Dolcini, Enrico
Abstract: Aim of the paper is to present the methodology used to develop a new process, based on high-pressure resin transfer molding (HP-RTM), to produce full carbon reinforced plastic rims for sports car. These components are nowadays made by pre-preg autoclave processing, which is expensive and time-consuming, so that they are basically sold as aftermarket option. The proposed technology allows a manufacturing volume high enough to be suitable for series production. In this paper, the resin and fiber selection criteria and tests are shown, as regards the mechanical properties, durability and injection strategies.